Critical Thinking in Academic Reading: EFL Students’ Perceptions and Challenges - Maab, Siti Husna; Ramadhanti, Safira Fauzia; Payung, Naftalia Fani; Yulia, Yuyun (Universitas Hamzanwadi, 2024)
Academic reading and critical thinking are pivotal in higher education, particularly for university students, including those who are English as a Foreign Language (EFL) learners. This study explores the perceptions of second-semester English Education students at Yogyakarta State University regarding the interrelationship between academic reading and critical thinking skills. It identifies the challenges they face in this area. The research involved 19 participants and employed a mixed-methods design, utilizing both Likert-scale questionnaires and semi-structured interviews for data collection. The data were analyzed through descriptive statistics and thematic analysis. Results indicate that participants generally hold positive views about their critical thinking and academic reading capabilities across all aspects of Bloom's Taxonomy. The findings suggest a correlation between students proficient in academic reading and those who exhibit strong critical thinking skills. They expressed confidence in their ability to understand, evaluate, and analyze texts. Furthermore, the study reveals that these students face several challenges, such as language complexities, interdisciplinary comprehension issues, and subjective biases, which affect their learning processes in critical thinking and academic reading.